2004
DOI: 10.1523/jneurosci.0845-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of Visual System Development by Environmental Enrichment

Abstract: Thus far, the developmental plasticity of the visual system has been studied by altering or reducing visual experience. Here, we investigated whether a complex sensory-motor stimulation, provided by rearing animals in an enriched environment, affects visual system development. We found that raising mice in this condition causes an earlier eye opening, a precocious development of visual acuity, and an accelerated decline of white matter-induced long-term potentiation. These effects are accompanied by a precocio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
219
2
13

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 242 publications
(252 citation statements)
references
References 40 publications
18
219
2
13
Order By: Relevance
“…Previous studies have shown inconsistent results as to how environmental enrichment impacts on pup licking/grooming of dams. While some (Cancedda et al 2004) found significantly more licking/grooming for female mice living in an enriched environment, others (Welberg et al 2006) did not report any enrichment-induced changes in the amount of pup licking/grooming in rats. The latter would be in line with the present results, although the overall reduced nursing time, alongside the increased time spent eating and drinking, would rather suggest a decreased maternal care.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Previous studies have shown inconsistent results as to how environmental enrichment impacts on pup licking/grooming of dams. While some (Cancedda et al 2004) found significantly more licking/grooming for female mice living in an enriched environment, others (Welberg et al 2006) did not report any enrichment-induced changes in the amount of pup licking/grooming in rats. The latter would be in line with the present results, although the overall reduced nursing time, alongside the increased time spent eating and drinking, would rather suggest a decreased maternal care.…”
Section: Discussionmentioning
confidence: 96%
“…However, measuring gross locomotor activity, although non-invasive, does not detect subtle locomotor effects, or provides qualitative insights, e.g., if activity in the pups was more directed towards to or away from objects. Effects primarily on sensory processing (Cancedda et al 2004) cannot be excluded either.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most relevant result was the demonstration that EE from birth induces a marked acceleration in the maturation of VA, an effect consistently reported in mice and rats using both electrophysiological and behavioural methods. [33][34][35][36] The acceleration effect is quite strong, yielding a 1-week advance in the time course of VA maturation with respect to control animals. This functional outcome is accompanied by a precocious decline in the possibility of inducing LTP of layer II-III field potentials after theta-burst stimulation of the white matter (WM-LTP) in the visual cortex, 34 a well-established in vitro model of developmental plasticity.…”
Section: Influence Of Ee On Brain Developmental Plasticitymentioning
confidence: 99%
“…40,41 Indeed, mice raised in EE show increased levels of the BDNF protein in their visual cortex at P7, 34,35 revealing the fact that neurotrophin BDNF is one of the crucial factors that underlie EE effects on V1 maturation. In both BDNF overexpressing mice and EE pups, higher BDNF levels were also shown to trigger the maturation of the inhibitory GABAergic system, which, by affecting receptive field development and synaptic plasticity, could determine both the accelerated maturation of VA and the decline of cortical plasticity.…”
Section: Influence Of Ee On Brain Developmental Plasticitymentioning
confidence: 99%